ROOT CAUSE PROBLEM SOLVING (RCPS) ANALYSIS AS AN OPTIMIZATION OF GENERAL CATEGORY ELECTRICITY BILL ARREARS CONTROL STRATEGY AT PT PLN (PERSERO) UNIT LAYANAN PELANGGAN BANYUMAS - Fransiska Sinaga; Sri Murni Setyawati; Rio Dhani Laksana (INTERNATIONAL PENELITI EKONOMI, SOSIAL, DAN TEKNOLOGI, 2020)
PT PLN (Persero) ULP Banyumas is one of the work areas of PT PLN (Persero) UID Jawa Tengah dan DIY. One of the challenge in PLN Banyumas is bill arrears. Electricity bill arrears can result in income being not smooth. The cause of arrears in the PLN Banyumas especially the general category is the culture of the customer, many of the customers pay the electricity bill accumulatively and wait to be billed by the termination officer. There are also other causes, namely termination officers who have not been consistent in applying the rules. Handling the problem regarding arrears is formulated the cause and the selection of solutions that can be done using Root Cause Problem Solving (RCPS). The results of the RCPS analysis in several solutions that could be done to reduce arrears, namely optimization of the implementation of power termination, timely billing and socialization of payment of electricity bills, socialization of replacement to prepaid electricity, and optimization of CMC to termination officers. After the activity has been carried out, there has been an increase in the performance of bills arrears in the general category between quarter 3 and 4 of 2018.